A strategic sustainability model for global luxury companies in the management of CO2 emissions - Rangel Pérez, Celia; López, Belén; Fernández, Manuel (Springer, 2024)
Luxury brands are at the forefront of sustainability efforts and carbon emission reductions to fight climate change. The goal of this paper is to analyze such climate change challenges in terms of cost efforts within large luxury conglomerates. In doing so,financial metrics have been gathered for the top 100 companies in the luxury sector and compared against CO2 emissions metrics with regressive methods. This enables the study of relationships between sustainability and finance to explore if sustainability is expensive and if sustainability is explained by costs,sales,taxes,or investment. Such works allow the setting of conclusions on financial and managerial decisions and,moreover,set a new framework of analysis based on financial variables and the positive or negative impact on CO2 emissions,such as which financial variables generate more CO2 emissions (luxury sales,capital investment and financial cost) and which help to reduce such emissions (cost of goods sold,general expenses and taxes). © The Author(s) 2024.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura; ODS 13 - Acción por el clima